2009
DOI: 10.1017/s0007114509317420
|View full text |Cite
|
Sign up to set email alerts
|

Breast-feeding and adherence to infant feeding guidelines do not influence bone mass at age 4 years

Abstract: The impact of variations in current infant feeding practice on bone mineral accrual is not known. We examined the associations between duration of breast-feeding and compliance with infant dietary guidelines and later bone size and density at age 4 years. At total of 599 (318 boys) mother -child pairs were recruited from the Southampton Women's Survey. Duration of breast-feeding was recorded and infant diet was assessed at 6 and 12 months using FFQ. At 6 and 12 months the most important dietary pattern, define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 27 publications
6
45
0
Order By: Relevance
“…There are less data in healthy children. Harvey et al [23] reported no association at age 4 years, and we have previously reported a beneficial association of breastfeeding for both bone mass [24] and fractures [25] up to age 8 years in children, especially in those born at term. Other observational studies with bone measures at younger ages did not demonstrate associations between breastfeeding and bone density [19].…”
Section: Breastfeedingmentioning
confidence: 50%
“…There are less data in healthy children. Harvey et al [23] reported no association at age 4 years, and we have previously reported a beneficial association of breastfeeding for both bone mass [24] and fractures [25] up to age 8 years in children, especially in those born at term. Other observational studies with bone measures at younger ages did not demonstrate associations between breastfeeding and bone density [19].…”
Section: Breastfeedingmentioning
confidence: 50%
“…First, both exclusive and total breastfeeding duration did not differ between groups. Second, previous studies have shown that breastfeeding has instead a positive 34 or neutral [35][36][37] effect on prepubertal bone mass. Finally, comparison of BMD between breastfed and formulafed children for each group revealed no differences (data not shown).…”
Section: Resultsmentioning
confidence: 98%
“…In one observational study, breastfeeding for more than 7 months resulted in lower TB BMD, LS bone area, and LS BMC at age 32 years in males, but not females [56] . However, breastfeeding duration was not associated with bone density outcomes at age 4 in a different cohort [57] .…”
Section: Breastfeedingmentioning
confidence: 72%